Scientific substantiation of the technology of the functional beverage, based on the rowan juice with vegetative extracts use - Stetsenko, Natalia; Goyko, Iryna (My University, 2021)
Modern manufacturers of food and beverages are faced with the task of creating a new generation of food products - health-improving and functional products that can positively influence the health of consumers. Purpose and methods. The aim of the work is to substantiate the choice of rowan juice for creating a functional drink, determining its composition and physicochemical indicators, selecting effective prescription components of antioxidant action and developing a formulation of a non-alcoholic drink with health-improving properties. The work used standard organoleptic, physicochemical and computational research methods. Results. It was proved that it is advisable to use rowan juice as the basis for functional juice drinks. For maximum juice extraction, it is necessary to pre-freeze the raw material, followed by its crushing and processing with an enzyme preparation. Green tea and sage extracts, which are sources of substances with antioxidant properties, were selected to combine with rowan juice. Conclusions and discussion. It has been established that non-alcoholic juice-containing drink belongs to the category of functional food products, since when consumed, the level of providing daily requirements for ascorbic acid, β-carotene, pectin, bioflavonoids, catechins is within 10 ... 50%. The scientific novelty of the research lies in the development of the formulation of a juice-containing functional drink based on rowan juice with the addition of plant extracts. The practical significance of the results obtained is expressed in the fact that they can be used at enterprises producing non-alcoholic beverages, in establishments of a restaurant industry, sanatorium-resort and healthy food. Перед сучасними виробниками харчових продуктів та напоїв стоїть завдання створення харчових продуктів нового покоління – оздоровчих та функціональних продуктів, здатних позитивно впливати на стан здоров’я споживачів. Мета і методи. Метою роботи є обґрунтування вибору соку горобини для створення напою функціонального призначення, визначення його складу та фізико-хімічних показників, підбір ефективних рецептурних компонентів антиоксидантної дії та розроблення рецептури безалкогольного напою з оздоровчими властивостями. У роботі використані стандартні органолептичні, фізико-хімічні та розрахункові методи досліджень. Результати. Було обґрунтовано, що сік горобини доцільно використовувати як основу соковмісного напою функціонального призначення. Для максимального вилучення соку необхідно проводити попереднє заморожування сировини з подальшим її подрібненням та обробкою ферментним препаратом. Для комбінування із соком горобини обрано екстракти зеленого чаю та шавлії, які є джерелами речовин з антиоксидантними властивостями. Висновки та обговорення. Встановлено, що безалкогольний соковмісний напій належить до категорії функціональних харчових продуктів, оскільки при його вживанні рівень забезпечення добових потреб у аскорбіновій кислоті, β-каротині, пектині, біофлавоноїдах, катехінах знаходиться у межах 10…50%. Наукова новизна одержаних результатів полягає у розробленні рецептури соковмісного функціонального напою на основі соку горобини з додаванням рослинних екстрактів. Практичне значення одержаних результатів виявляється у тому, що їх можна використовувати на підприємствах, що випускають безалкогольні напої, у закладах ресторанного господарства, санаторно-курортного та здорового харчування.
Keywords: juice drink; rowan juice; green tea extract; sage extract; functional drink; biological value; antioxidant properties; соковмісний напій; сік горобини; екстракт зеленого чаю; екстракт шавлії; функціональний напій; біологічна цінність; антиоксидантні властивості; кафедра технології оздоровчих продуктів